2015
DOI: 10.5742/mejn.2015.92618
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer , Breast Self - Examination Knowledge among Female High School Students in Riyadh City

Abstract: Breast cancer (BC) is the most prevalent form of cancer in the Kingdom of Saudi Arabia, accounting for 11% of all female cancers. It is considered to be a progressive disease with a poor prognosis if detected late. The low level of knowledge and practice of breast self-examination is an important method of prevention. The study was aimed at assessing the knowledge of breast cancer and practice of Breast Self-Examination (BSE) among female secondary school students in Riyadh city. Material & Methods : A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
5
13
3
Order By: Relevance
“…However, a study reported that less than 1% of the participants had very good knowledge and more than 30% of the study population had poor to very poor knowledge (Hadi et al 2010). This is similar to the other studies where most of young females had a low level of knowledge in relation to breast cancer prevention (Akhtari-Zavare et al 2015;Che Mut et al 2018), where the secondary school girls had very low knowledge on breast cancer and BSE practice (Al-Haji & Moawed 2015;Che Mut et al 2019). In addition, the most important information on breast cancer which is the knowledge on signs and symptoms of breast cancer are also poor among young women.…”
Section: Introductionsupporting
confidence: 61%
“…However, a study reported that less than 1% of the participants had very good knowledge and more than 30% of the study population had poor to very poor knowledge (Hadi et al 2010). This is similar to the other studies where most of young females had a low level of knowledge in relation to breast cancer prevention (Akhtari-Zavare et al 2015;Che Mut et al 2018), where the secondary school girls had very low knowledge on breast cancer and BSE practice (Al-Haji & Moawed 2015;Che Mut et al 2019). In addition, the most important information on breast cancer which is the knowledge on signs and symptoms of breast cancer are also poor among young women.…”
Section: Introductionsupporting
confidence: 61%
“…Breast cancers, unlike most others, occur in an organ (breast) that is easily visible [ 9 , 14 ], and BSE is the visual and manual examination of breasts for lumps, bumps, and skin changes over nipples and breasts [ 4 ]. Monthly BSE is recommended from age 20 [ 4 ], Even though its efficacy in preventing breast cancer deaths is unproven [ 15 , 16 ], it remains a free, painless and easy-to-practice technique, which helps improve body awareness, allowing changes potentially indicative of breast cancer to be picked up early [ 17 , 18 ]. Alongside other screening methods, BSEs can improve outcomes and reduce mortality by as much as 25% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the mean age of presentation in Nigeria is 42 to 44 years [ 2 , 26 , 31 ], prognosis in younger patients aged < 40 years is poor [ 32 ], and early screening and detection is vital [ 17 ]. While reports vary, one study found that 12% of the cancers in Nigeria are among those aged < 30, the youngest being a 16 year old [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a scale from one to five the overall perceived level was moderate (M=3; SD =1.07) on a 5-point Likert-type scale. Generally, we can consider that items that have a mean equal or more the 3 have more agreement as perceived by the participant; those items include item number 5,12,13,10,11,14,15,4,18,1,7,9,8,6,19,26; those items are arranged from the most agreed items to the less agreed items by the participants. On the other hand, items that have a mean less than 3 have less agreement as perceived by the participants; those items include item number 3,16,20,22,2,21,17,25,24,23; those items are arranged from the most agreed items to the less agreed.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence rate of BC is increasing in rich developing country due to increase life expectancy, increase urbanization and adoption of western lifestyles [6]. In Saudi Arabia (SA) which is a rich Arab gulf country BC is high prevalence type of cancer which accounting for about 11% of all women cancer cases [7]. Cancer in Riyadh City The more recent report by Saudi general authority of statistics showed 43% of total population was female [8] which indicate the required need to investigate their perception toward BC.…”
Section: Introductionmentioning
confidence: 99%